2009
DOI: 10.1080/00207540903160766
|View full text |Cite
|
Sign up to set email alerts
|

Empirical analysis of maintenance performance measurement in Belgian industries

Abstract: Performance measurement is a fundamental instrument of management. For maintenance management, one of the key issues is to ensure the maintenance activities planned and executed have given the expected results. This can be facilitated by effective use of rigorously defined key performance indicators (KPI) that are able to measure important aspects of maintenance function. In this paper, an industrial survey was carried out to explore the use of performance measurement in maintenance management. Based on survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 18 publications
4
71
0
1
Order By: Relevance
“…Well-defined indicators can potentially support the identification of current and desired performance and provide us with information on the progress of individual performances. In addition, it can be a link between strategy and management, thereby promoting the establishment and implementation of initiatives related to the improvement of the company (Maria, 2009;Muchiri et al, 2010;Hornungová, 2014b). Performance measurement supports corporate day-to-day activities to reach strategic goals.…”
Section: Main Textmentioning
confidence: 99%
“…Well-defined indicators can potentially support the identification of current and desired performance and provide us with information on the progress of individual performances. In addition, it can be a link between strategy and management, thereby promoting the establishment and implementation of initiatives related to the improvement of the company (Maria, 2009;Muchiri et al, 2010;Hornungová, 2014b). Performance measurement supports corporate day-to-day activities to reach strategic goals.…”
Section: Main Textmentioning
confidence: 99%
“…It is not until recently, when practical attempts have been made to deal with the relationship between maintenance strategies and the overall business objective of organizations (Tsang 2002, Pinjala and Pintelon 2006, Muchiri et. al.…”
Section: Development Of Maintenance Policies By Considering Life Cyclmentioning
confidence: 99%
“…Pinjala et al (2006) discuss the relationship between an organization's business objectives and some of the maintenance activities and Khan (2001) presents that system reliability is related to LCC. A strategic approach to making maintenance strategies and policies has been recognized especially in capital-intensive industries (Tsang, 2002;Pinjala et al, 2006;Muchiri et al, 2010).…”
Section: Development Of Maintenance Policies By Considering Life Cyclmentioning
confidence: 99%
See 1 more Smart Citation
“…The references have also been reviewed for the measures used for the machine effectiveness evaluation in an industrial sector [24,33]. The correlation of the selected indicators with other evaluation methods was assessed as well [2,24].Moreover, the analysis of the references showed that there were also studies conducted concerning maintenance activities based on the MTTF values obtained [22]. The study, that was carried out, also regarded the evaluation of the OEE measure values obtained [2,18], the possibilities of its improvement [31,39] as well as its computer based (automated) calculation [30].…”
mentioning
confidence: 99%